Upaya Meningkatkan Pemahaman Konsep pada Pembelajaran Fikih dengan Model Pembelajaran Kooperatif Tipe Student Facilitator and Explaining - Mahmudah Mahmudah (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine (1) efforts to improve conceptual understanding of Islamic Jurisprudence learning materials using the Student Facilitator and Explaining cooperative learning model in class VIII MTs Miftahul Huda Lehan, (2) improving conceptual understanding of Islamic Jurisprudence learning materials in class VIII MTs Miftahul Huda Lehan using the Student Facilitator and Explaining cooperative learning model.This research is a classroom action research (CAR). The subjects of the research used were 32 students of class VIII MTs Miftahul Huda Lehan in the even semester of the 2024/2025 academic year. This research was conducted in two cycles consisting of cycle I (1 meeting) and cycle II (2 meetings). Data collection techniques used observation sheets, tests and documentation. Data analysis techniques used qualitative and quantitative descriptive techniques. The criteria for the success of this research, namely student learning activity, is said to be successful if an average percentage of 70% of the number of students in one class who are active in learning activities is obtained. While student learning outcomes of at least 75% of the number of students have met the Minimum Completion Criteria (MCC) of 75.The results of the study showed that the use of the Student Facilitator and Explaining cooperative learning model in class VIII MTs Miftahul Huda Lehan succeeded in improving students' understanding of concepts in the Fiqh learning material.